Barriers and enablers for oral health promotion programs amongst primary healthcare stakeholders in Qatar - a qualitative investigation - Asmaa Othman Alkhtib; Kamran Ali; Anand K. Sajnani; Lamyia Anweigi (BMC, 2023)
Abstract Background Oral health of preschool children remains a concern globally. Primary healthcare providers are in a vital position to support preventive oral care programmes. This study explored current practices, perception and barriers of primary health care professionals towards oral health promotion program of children in Qatar. Methods The qualitative research used focus group discussions and interviewed a total of 108 participants that were audio recorded and transcribed verbatim. Four major themes emerged and were analysed to explore contextual patterns within the data. Results Participants acknowledged the high prevalence of caries in children and identified the causes in the local context which included parental practices, poor dietary habits, impact of culture lack of oral health knowledge, limitations in the healthcare system, and negative role of the media. However, complex barriers were exposed, including lack of time and ownership, system coordination between organizations, and lack of policy. Conclusion Health professionals and bureaucrats involved in decision-making held a positive attitude towards oral health prevention programs and were enthusiastic to initiate and support these programs.